Moderating Role of Leaders’ Emotional Intelligence in Job Characteristics and Employees’ Organizational Citizenship Behavior Relationship: Evidence from Construction Sector of Pakistan - Muhammad Asadullah; Dr. Kamran Azam; Rohi Mehnaz; Dr. Mujahid Hussain (Journal of Business & Tourism, 2021)
The present study investigates the moderating role of leaders’ EI on Oldham and Hackman’s Job Characteristics and Employees’ OCB relationship in construction sector of Pakistan. Questionnaires were completed by 187 participants employed in private construction sector organizations in Islamabad using simple random sampling. Linear Regression Model was applied to predict the value of the dependent variable ‘OCB’ on the basis of independent variables Task Significance, Skill Variety, Task Identity, Job Autonomy and Feed-Back. Stepwise Multiple Regression Model was applied to test the moderating effect of EI in OCB-JC relationship. On the basis of the results, it was established that employees’ OCB can be significantly predicted based upon core job characteristics of Hackman & Oldham (1976). It was further established that leaders’ EI moderates the Job Characteristics - OCB relationship.